2002
DOI: 10.1046/j.1365-2265.2002.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography for preoperative localization of enlarged parathyroid glands in primary hyperparathyroidism: comparison with 99mtechnetium sestamibi scintigraphy

Abstract: Ultrasonography can be a sensitive and accurate method for preoperative localization of enlarged parathyroid glands in primary hyperparathyroidism, comparable in overall utility to sestamibi scintigraphy. These results suggest that a strategy of initial testing with one or the other method, followed by the alternate imaging test if the first test is negative, would provide correct parathyroid imaging in most patients without prior parathyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
122
4
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 26 publications
14
122
4
4
Order By: Relevance
“…Commonly used modalities include ultrasound, CT or magnetic resonance imaging, and technetium sestamibi scintigraphy. Ultrasound is commonly used due to its low cost and convenience, but it has poor sensitivity (≤30%) for locating ectopic glands (14). Even the sensitivity for localization of enlarged parathyroid glands in the normal anatomical location varies greatly (44 to 87%) and depends on operator skill and experience (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used modalities include ultrasound, CT or magnetic resonance imaging, and technetium sestamibi scintigraphy. Ultrasound is commonly used due to its low cost and convenience, but it has poor sensitivity (≤30%) for locating ectopic glands (14). Even the sensitivity for localization of enlarged parathyroid glands in the normal anatomical location varies greatly (44 to 87%) and depends on operator skill and experience (14).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is commonly used due to its low cost and convenience, but it has poor sensitivity (≤30%) for locating ectopic glands (14). Even the sensitivity for localization of enlarged parathyroid glands in the normal anatomical location varies greatly (44 to 87%) and depends on operator skill and experience (14). In comparison, parathyroid scintigraphy and CT imaging have a much higher sensitivity than ultrasound for localizing parathyroid adenoma (71 to 93% and 76 to 83%, respectively) (14) and the sensitivity can be up to 100% when parathyroid scintigraphy and CT imaging are used in combination (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although dual-phase dual-isotope iodine 123 ( 123 I)/technetium Tc 99m ( 99 mTc) sestamibi scintigraphy and ultrasonography and their comparison for determination of enlarged parathyroid glands in primary hyperparathyroidism has been discussed in many studies, their utility in renal hyperparathyroidism is rarely addressed [29,30]. Périé et al [31] reported that a series of 20 patients consecutively referred for parathyroidectomy, hyperplastic parathyroid glands were detected by USG in 75%, dual-phase 123 I/ 99 mTc sestamibi scintigraphy in 66%, and both methods in 88%.…”
Section: Discussionmentioning
confidence: 99%
“…As hiperplasias glandulares podem não ser identificadas ao ultrassom e cintilografia, sendo importante, neste caso, a exploração de todas as glândulas durante o ato cirúr-gico (25). Os dois métodos em conjunto auxiliam na localização de glândulas ectópicas (27,28). Conforme observado em nossos casos, o ultrassom, nos cinco pacientes que o realizaram, foi conclusivo e compatível com os achados pós-operatórios, estando nestes a cintilografia negativa.…”
Section: Discussão E Conclusõesunclassified